2017
DOI: 10.1002/2016jc012055
|View full text |Cite
|
Sign up to set email alerts
|

Direct estimates of friction factors for a mobile rippled bed

Abstract: New friction factor estimates are computed from the total momentum transfer applied to a rippled sediment bed. The total time‐dependent momentum flux is achieved by implementing the double‐averaged horizontal momentum equation on the nearbed flow field collected with PIV. Time‐independent friction factors are obtained by regressing the total momentum flux to the common quadratic stress law given by 12ρu∞|u∞|. The resulting friction factors compare favorably with available analysis techniques including energy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(19 citation statements)
references
References 35 publications
2
17
0
Order By: Relevance
“…The large‐scale overturning jets of breaking waves provide comparable downward momentum for vortices to significantly alter truew˜. This is confirmed with the findings in Wilson et al () and Rodriguez‐Abudo and Foster (), in which the presence and ejection of vortices from wave breaking can significantly change the WSS. Moreover, Vander et al () measured the cross‐shore variation of WSS across a fixed bar.…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…The large‐scale overturning jets of breaking waves provide comparable downward momentum for vortices to significantly alter truew˜. This is confirmed with the findings in Wilson et al () and Rodriguez‐Abudo and Foster (), in which the presence and ejection of vortices from wave breaking can significantly change the WSS. Moreover, Vander et al () measured the cross‐shore variation of WSS across a fixed bar.…”
Section: Discussionsupporting
confidence: 86%
“…Zou et al (, ) further developed a generalized solution of WSS distribution incorporating the effects of bottom slope and wave breaking, accounting for bottom dissipation with coupled wave and boundary layer flow. Moreover, several laboratory studies (De Serio & Mossa, ; Rodriguez‐Abudo & Foster, ; Ting & Nelson, ; Vander et al, ) and field studies (Elgar et al, ; Wilson et al, ; Zou et al, ) have confirmed that the magnitude of WSS is measurable. However, the measured magnitude and vertical distribution of WSS vary significantly in previous studies.…”
Section: Introductionmentioning
confidence: 91%
See 3 more Smart Citations